Efektivitas Penyidikan dan Perlindungan Korban Cybercrime : Studi Kasus Polres Magelang Kota - Aura Zahra Rizkillah Latif; Hasrinda Rizqi Pramassari; Najwa Aulia Widyaningrum; Ayu Savitri; Muhammad Reyvanza Anwar; Syifaa Afelyna Suryoputri (Lembaga Pengembangan Kinerja Dosen, 2026)
This study analyzes the effectiveness of cybercrime investigation, particularly online fraud, at Polres Magelang Kota, highlighting the legal gap between das sollen (ideal regulations in National Criminal Code Article 492, ITE Law, and updated KUHAP) mandating swift tech-based forensics and das sein (field reality) relying on manual methods, limited digital forensic HR, inadequate equipment, and poor inter-agency coordination, resulting in only 81.72% case resolution rate. The objectives are to evaluate Satreskrim's investigation process, victim protection, and formulate strategic recommendations to achieve the national 90% target. Employing normative-empirical qualitative methods with das sollen-das sein approach, data collection involved library research, field observations, investigator interviews, and case studies like the 2025 student phone seizure. Findings reveal structured yet hindered investigations due to structural constraints, with cumulative victim protections via restitution and restorative justice rarely fully realized. Conclusions emphasize AI training, local MoUs, and massive digital literacy campaigns to bridge Friedman's legal system theory gaps and enhance local cybercrime enforcement.